Sleep Disorders in Blind Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The frequency and type of sleep disorders in 77 blind children, from 3 to 18 years of age, were compared with 79 matched controls, using a 42-item questionnaire in a study at the Stanford University Sleep Disorders Center, Stanford, CA, and the Laboratoire du Sommeil, Centre Hospitalier Universitaire de l'Hotel-Dieu a Paris, France.